ANALISA PROKSIMAT DAN NILAI KALOR PADA BRIKET BIOARANG LIMBAH AMPAS TEBU DAN ARANG KAYU - Eddy Elfiano; Purwo Subekti; Ahmad Sadil (Universitas Pasir Pengaraian, 2014)
In this study, waste of bagasse and wood charcoal was converted into charcoal briquettes to be used as an alternative fuel. The bagasse and wood charcoal were selected as raw material to produce briquette due to these two materials was abundantly available and because they have not been used in any application. Moreover, the use of them as briquette and alternative energy will reduce the accumulation of waste that causes environmental pollution. Analysis of proximate test and heating value test showed that the percentage of moisture content of bagasse briquettes withdammar as adhesive is 3.36 to 1.47%, the amount of volatile matter is 36.91 to 30.15%, the ash content is 8.05 to 6.10 % and heating value is 3683.68 to 4520.88 kJ / kg. As for the charcoal briquettes was obtained that percentage of moisture content is 3.25 to 1.36 %, content of volatile matter is 34.55 to 26.53%,ash content is 6.36 to 5.37%, and heating value is 3934.84 to 5274.36kJ/kg.